The case for grounding biblical hermeneutics upon the diachronic method - Levinson Bernard M. (Acta Universitatis Szegediensis de Attila József nominatae : papers in english and american studies, 1992)
Recent developments within Hebrew Bible scholarship, in particular, the emergence of a new „literary criticism", promised a renewed concern with key interpretive issues that too frequently have been bypassed by the more conventional diachronic (historical-critical) method. The new approach, because of its emphasis upon a synchronic methodology, treats the biblical text as a coherent product of authorial intentionality, similar to a contemporary literary complexity. The newer synchronic method tends to disavow the classical questions of „Higher" or „Lower" Criticism: establishing the date and historical context of the text, distinguishing separate literary sources within it, analyzing text-critical or redactional issues, and so on. The intellectual origins, the methodological implications, and the hermeneutical presuppositions of this new method, which is increasingly becoming the norm for those scholars concerned with questions of interpretation and hermeneutics, have received little critical examination. The paper on which my presentation is based attempts to help fill this gap. Using Meir Sternberg's The Poetics of Biblical Narrative (1985) as a point of departure, the paper has a triple focus: To provide the context for the emergence of the new synchronic approach as a reaction against the failure of diachronic analysis to address questions of coherence and meaning. The synchronic approach in many ways backtracks behind the early modern period to adopt a pre-critical biblical hermeneutics as a ploy against the historical method. To demonstrate that the synchronic method contradicts its own mandate. By rejecting diachronic analysis as essentially irrelevant (as merely providing access to background or to „context" rather than „text"), the synchronic method cannot achieve its avowed goal of providing an adequate conceptualization of the biblical text. An examination of the biblical flood story (Genesis 6 — 9) reveals important literary aspects of the text unavailable to a purely synchronic method. Precisely those aspects, as revealed by a diachronic method, are indispensable any theoretical statement concerning ancient Israelite notions of textual coherence and complexity. To show that the synchronic method, in basing itself almost entirely on biblical narrative or poetic texts, further removes its own ground in attempting to provide anadequate hermeneutics of the Hebrew Bible. The legal corpora of the Bible, essentially ignored by the new approach, not only are clearly „literary" in their composition and structure, but also provide essential access to Israelite notions of authorship, interpretation, and textual authority. On these counts, any adequate future hermeneutics of the Hebrew Bible must be grounded conjointly upon the synchronic and the diachronic methods and, no less conjointly, upon law and narrative.